Improving the Proactive Routing Protocol using Depth First Iterative Deepening Spanning Tree in Mobile Ad Hoc Network - Justin Sophia I; N. Rama (Institute of Advanced Engineering and Science, 2017)
Owing to the wireless and mobility nature, nodes in a mobile ad hoc network are not within the transmission range. It needs to transfer data through the multi-intermediate nodes. Opportunistic data forwarding is an assuring solution to make use of the broadcast environment of wireless communication links. Due to absence of source routing capability with efficient proactive routing protocol, it is not widely used. To rectify the problem, we proposed memory and routing efficient proactive routing protocol using Depth-First Iterative-Deepening and hello messaging scheme. This protocol can conserve the topology information in every node in the network. In experimental analysis and discussion, we implemented the proposed work using NS2 simulator tool and proved that the proposed technique is performed well in terms of average delay, buffer and throughput.